Staphylococcus caprae bone and joint infections: a re‐emerging infection?. (29th July 2014) - Seng, P.; Barbe, M.; Pinelli, P. O.; Gouriet, F.; Drancourt, M.; Minebois, A.; Cellier, N.; Lechiche, C.; Asencio, G.; Lavigne, J. P.; Sotto, A.; Stein, A.; et al.
Abstract Staphylococcus caprae has been recently classified as a human pathogen, but the incidence of S. caprae in human bone and joint infections (BJIs) is under‐reported. In this study, we report 25 cases of S. caprae BJI, and we review the 31 cases published in the literature. Molecular techniques and matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry improved the identification of clinically relevant S. caprae strains. In this study, 96% of S. caprae BJIs were localized to the lower limbs, and 88% of the cases involved orthopaedic device infections. S. caprae joint prosthesis infections (JPIs), internal osteosynthesis device infections (I‐ODIs) and BJIs without orthopaedic device infections were recorded in 60%, 28% and 12% of cases, respectively. Ten (40%) S. caprae BJIs were polymicrobial infections. These infections were associated with past histories of malignancy (p 0.024). Of the 14 bacterial species related to S. caprae BJI, 57% were staphylococci. I‐ODIs were significantly associated with polymicrobial infections (p 0.0068), unlike JPIs, which were monomicrobial infections (p 0.0344). Treatment with rifampicin and fluoroquinolone was recorded in 40% of cases. Surgical treatment was performed in 76% of cases, e.g. prosthesis removal (36%), osteosynthesis device removal (24%), and surgical debridement (16%). Thirty per cent of cases were not treated. Relapses were observed mainly in the patients treated by surgical debridement only (p 0.033). In summary, S. caprae BJI is an underestimated hospital‐acquired emerging infection. S. caprae BJI is correlated with infections in orthopaedic devices, which must be removed to control the infection.